Identification of Group "A & AB" Major Sub-Groups in a Mixed Pakistani Population of Karachi - Nadeem Nusrat, Asma Shaikh, Muhammed Akbar Agha, Saddam Hussain Kalwar, Saima Minhas, Khaleeque-u-Nisa, Zeeshan-ul-Qadar, Rafique Khannani , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To determine the frequency of weaker sub-group A2 and A2B in the catchment area of Dow international medical college, Karachi. Place & Duration: Observational cross sectional study conducted in Dow diagnostic research and reference lab ( DDRRL ) blood bank from 1st January 2013 till 30th June 2013. Material and methods: A total of 1424 healthy unrelated donors and their patients for whom they donated blood, of both sexes and reporting to DDRRL blood bank were selected. Forward and reverse ABO grouping was done and as A and AB blood groups were isolated. These groups were then tested for sub-group A2 and A2B and their numbers were expressed as percentages of their respective blood groups. Results: Amongst 387 A group individuals, n= 362 (93.54 %) were Al while n=25 (6.46 %) were A2 sub-group. From AB n= 101, n = 85 (83.17 %) belonged to AlB sub-group while n=17 (16.83 %) were A2B sub-group Conclusion: There is substantive presence of the most frequently occurring subgroups, Al, A2, Al B and A2B in Pakistani population and their frequency is nearly the same as reported in literature